Nutrition Education for Babies and Toddlers - Marsanti, Avicena Sakufa; Handayani, Prita; Yuniana, Amama; Seka, Arum; Anindita, Dhea; Afrida, Diza; Alfi, Fahida; Anuraga, Gita (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: Providing education to the community so that partner communities have the ability and success in implementing efforts and actions to prevent malnutrition in Balerejo Village, Kawedanan District, Magetan Regency. Method: The method of this activity is providing education and motivation with the theme